Performance Analysis for Lossy-Forward Relaying Over Nakagami- m Fading Channels - Shen Qian; Xiaobo Zhou; Xin He; Jiguang He; Juntti, Markku; Matsumoto, Tad (IEEE transactions on vehicular technology, 2017)
We investigate the performance of three-node lossy-forward (LF) relaying over independent block Nakagami-m fading channels. Based on the theorem of source coding with side information, the exact outage probability expression for arbitrary values of the shape factor m is derived under the assumptions of both the Gaussian codebook capacity and the constellation constrained capacity. The difference in outage probability between the two codebook models of capacity is found to be very minor. Furthermore, an accurate high signal-to-noise ratio approximation for the outage probability is obtained. It clearly identifies the equivalent diversity order and coding gain of the LF relaying. It is shown that the LF relaying is superior to conventional decode-and-forward relaying in terms of the outage probability and the ϵ-outage achievable rate. Moreover, with the LF relaying, the optimal location for the relay (R), which minimizes the outage probability, is found to be the point having same distance to the source (S) and the destination (D) when the S-R and R-D links experience the same level of fading. The accuracy of the analytical results is verified by a series of Monte Carlo simulations.